Some Classes of Pseudosymmetric Contact Metric 3-Manifolds. (24th April 2012) - Moutafi, Evaggelia
Abstract : We study (a) the class of 3-dimensional pseudosymmetric contact metric manifolds with harmonic curvature and T r l constant along the direction of ξ and (b) the class of (κ, μ, ν )-contact metric pseudosymmetric 3-manifolds of type constant in the direction of ξ .